NORTH KOREA'S NUCLEAR THREAT TO UNITED STATES SECURITY DURING THE LEADERSHIP OF DONALD TRUMP - Danial Darwis Danial Darwis (Ikatan Dosen Menulis, 2022)
This paper attempts to look at the North Korean nuclear threat to the security of the United States during the presidency of the United States President Donald Trump by using the Security Dilemma, which is one of the concepts in realism theory that arises as a result of a country's actions to improve its country's security. Still, on the one hand, it creates a reaction. Other countries also want to improve their security, which will lead to a decrease in safety in the first country. In addition, the author also uses Balance of Power which underlies his view that every government or alliance of countries that feel threatened by increasing the military power of a country or a coalition of other countries will respond by increasing the strength of their country as a balancing effort. North Korea is again in the global spotlight for developing its nuclear program. This has created a reaction in the form of a security threat to the United States, so under the leadership of Donald Trump, various efforts have been made to offset this. This paper finds the results that the U.S. security dilemma is based on fear and threats due to the increasing power of North Korea. U.S. President Donald Trump tries to stop this by carrying out a Balance of Power. The forms of activity by Donald Trump include trying to combine diplomatic and sanctions with extreme measures in cutting economic resources, stopping food supplies, and diplomacy of isolation. Using military instruments to force Pyongyang to halt its nuclear weapons development program is also possible.